PENGARUHPENGGUNAAN MODEL PEMBELAJARAN ADVANCE ORGANIZER TIPE EXPOSITORYTERHADAP HASIL BELAJARMATEMATIKA SISWA KELAS X SMA PGRI METRO - Juitaning Mustika (Jurnal Karya Pendidikan Matematika, 2019)
The learning outcomes of class X SMA PGRI METRO students based on the Pre-survey results are still many who have not met the Minimum Completion Criteria (KKM) ≥ 65. In the learning process students are less active to ask questions and less accustomed to collaborating with other friends. One alternative learning is to use an advanced expository type organizer learning model. the advanced organizer type expository learning model is a learning model that directs students to the material they are going to learn by recalling concepts related to the previous material so that students are able to discover new knowledge by expanding the understanding of the basic concepts of students. So the purpose of this study was to determine the effect of using an expository type advanced organizer learning model on the learning outcomes of class X SMAPGRI Metro. This study uses a QuasiExperimental Design research design. The quasi-experimental design used in this study is Nonequivalent Control Group Design. The data obtained were analyzed descriptively statistically. The subjects of this study were the eleventh grade students of SMAPGRI Metro which numbered 26 students. The results showed that t count> t table is 6.802> 2.056 so that it rejects the null hypothesis (H_0). Based on the results of the study it can be concluded that: the advance organizer type expository learning model has an influence on student learning outcomes.